(Invited) Radiation Effects in AlGaN/GaN and InAlN/GaN High Electron Mobility Transistors. (13th April 2015) - Pearton, Stephen J.; Hwang, Ya-Hsi; Ren, Fan
Abstract : GaN HEMTs are more radiation hard than their Si and GaAs counterparts due to the high bond strength in III-nitride materials. We review data on the radiation resistance of GaN-based transistors such as AlGaN/GaN and InAlN/GaN High Electron Mobility Transistors (HEMTs) to different types of ionizin gradiation. The primary energy levels introduced by different forms of radiation, carrier removal rates and role of existing defects are discussed. The carrier removal rates are a function of initial carrier concentration, dose and dose rate but not of hydrogen concentration in the nitride material grown by Metal Organic Chemical Vapor Deposition. Proton and electron irradiation damage in HEMTs creates positive threshold voltage shifts due to a decrease in the two dimensional electron gas concentration resulting from electron trapping at defect sites, as well as a decrease in carrier mobility and degradation of drain current and transconductance. Neutron irradiation created more extended damage regions and at high doses leads to Fermi level pinning while 60Co γ-ray irradiation leads to much smaller changes in HEMT drain current relative to the other forms of radiation.